Measles virus-imposed remodeling of the autophagy machinery determines the outcome of bacterial coinfection. Issue 3 (4th March 2023) - Claviere, Mathieu; Lavedrine, Aude; Lamiral, Guénaëlle; Bonnet, Mariette; Verlhac, Pauline; Petkova, Denitsa S.; Espert, Lucile; Duclaux-Loras, Rémi; Lucifora, Julie; Rivoire, Michel; Boschetti, Gilles; Nancey, Stéphane; et al.
ABSTRACT: Although it is admitted that secondary infection can complicate viral diseases, the consequences of viral infection on cell susceptibility to other infections remain underexplored at the cellular level. We though to examine whether the sustained macroautophagy/autophagy associated with measles virus (MeV) infection could help cells oppose invasion by Salmonella Typhimurium, a bacterium sensitive to autophagic restriction. We report here the unexpected finding that Salmonella markedly replicated in MeV-infected cultures due to selective growth within multinucleated cells. Hyper-replicating Salmonella localized outside of LAMP1-positive compartments to an extent that equaled that of the predominantly cytosolic sifA mutant Salmonella . Bacteria were subjected to effective ubiquitination but failed to be targeted by LC3 despite an ongoing productive autophagy. Such a phenotype could not be further aggravated upon silencing of the selective autophagy regulator TBK1 or core autophagy factors ATG5 or ATG7. MeV infection also conditioned primary human epithelial cells for augmented Salmonella replication. The analysis of selective autophagy receptors able to target Salmonella revealed that a lowered expression level of SQSTM1/p62 and TAX1BP1/T6BP autophagy receptors prevented effective anti- Salmonella autophagy in MeV-induced syncytia. Conversely, as SQSTM1/p62 is promoting the cytosolic growth of Shigella flexneri, MeV infection led to reduced Shigella replication. The results indicate that the rarefaction of dedicated autophagy receptors associated with MeV infection differentially affects the outcome of bacterial coinfection depending on the nature of the functional relationship between bacteria and such receptors. Thus, virus-imposed reconfiguration of the autophagy machinery can be instrumental in determining the fate of bacterial coinfection.Abbreviations: ACTB/β-ACTIN: actin beta; ATG: autophagy related; BAFA1: bafilomycin A1 ; CFU: colony-forming units; CALCOCO2/NDP52: calcium binding and coiled-coil domain 2; FIP: fusion inhibitory peptide; GFP: green fluorescent protein; LAMP1: lysosomal associated membrane protein 1; LIR: MAP1LC3/LC3-interacting region; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MeV: measles virus; MOI: multiplicity of infection; OPTN: optineurin; PHH: primary human hepatocyte; SCV: Salmonella-containing vacuoles; SQSTM1/p62: sequestosome 1; S. flexneri: Shigella flexneri; S . Typhimurium: Salmonella enterica serovar Typhimurium; TAX1BP1/T6BP: Tax1 binding protein 1; TBK1: TANK binding kinase 1